(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2025)
The article presents the results of spatial generalization of hydrometeorological network data for the catchment areas of the Arctic rivers Taz, Pur and Nadym. The study is aimed at analyzing changes in air temperature and precipitation in the context of a reduction in the observation network and global warming. Based on meteorological station data, a significant positive temperature trend (0.023–0.033°C/year) was revealed, which was most pronounced in the northern regions. Precipitation analysis showed its non-uniform distribution and discrepancies between different data sources (UGMS and meteo.ru). Spatial interpolation methods confirmed the stability of temperature fields and high precipitation variability caused by local factors. The results obtained are important for understanding climate change in the Arctic and can be used to predict the hydrological regime of rivers.